A Message Of Loyalty to Maulana Khusraw (t 885 H) Study and Verification - Mhaidi , Raed (Islamic Sciences Journal, 2023)
Praise be to God, Lord of the worlds, and the best of prayers. Complete the greetings to our master Muhammad and his family and companions. The history of any nation or civilization is closely linked to its heritage and past, which is no secret to anyone that the heritage of our Islamic nation is abundant in manuscripts in various sciences, and among these sciences is the science of jurisprudence, and reviving it and bringing it out to the world is a duty of researchers, because many of these manuscripts are still Captives in cupboards or libraries, After researching and investigating these manuscripts, I found a treatise on jurisprudence by the scholar Mulla Khosrow, may God Almighty have mercy on him. It is “A Message on Loyalty,” and the content of this message, after reviewing it and verifying it, turned out to be a message that the Imam singled out in explaining the provisions of loyalty, especially At a time when Islamic conquests increased and jihad increased, which led to a large number of captives, the issue of loyalty spread. The nature of the research consisted of an introduction and two sections. The introduction mentioned the importance of the topic. As for the first topic, it was devoted to the study of the author and the research, with two demands, As for the imam, he divided the manuscript into the introduction, the purpose, the chapter. In conclusion, I ask God Almighty success in completing this message in the most complete manner.